The Impact of Covid-19 on the Performance of Hedge Funds Compared to Mutual Funds in South Africa - Muridili, Thonifho Pollen; Sgammini, Ruschelle; Ferreira-Schenk, Sune; Rensburg, John George Jansen van; Mokatsanyane, Daniel (International Journal of Economics and Financial Issues, 2022)
Investors are constantly searching for methods to generate value above passive investment techniques. Therefore, analysing the performance of hedge funds as compared to mutual funds, particularly in the wake of Covid-19, can aid investors in their investment decision-making process. Those investors who desire above-average returns, particularly in volatile market conditions place an expectation on hedge funds to be able to achieve higher performance during economic downturns, given that they are designed to mitigate risk and to take advantage of harsh financial market conditions. Monthly, secondary data were collected from 30 September 2018 to 31 August 2021 to analyse and compare the risk-adjusted performance of five hedge funds and five mutual funds in South Africa. Both hedge and mutual funds indicated higher risk-adjusted returns from the pre-Covid-19 period compared to during the pandemic. Hedge funds were found to have higher risk-adjusted returns than mutual funds during the Covid-19 period. The novelty of these results indicated that hedge fund managers can achieve higher returns for investors during extreme market events.